Partners in education : issues and trends from the 21st International Congress on the Education of the Deaf - Moores, Donald F. (Deaf education series, 2011)
"The contributors to this collection explore the many multifaceted challenges facing the world?s deaf students. Deaf children are being diagnosed with overlays of disabilities; more deaf children are growing up in poverty; and many deaf children represent minority racial/ethnic groups or are immigrants to their country of residence. The situation for deaf individuals in the most impoverished countries of the world is desperate and of crisis proportions. This volume brings these themes to light through its exceptional synthesis of the outstanding discourse that took place at ICED 2010, including abstracts from 30 celebrated conference presentations."